TECHNOLOGY OF DYNAMIC DATABASES CREATION WITH THE ENCLOSED STRUCTURES IN MS EXCEL - L.V. Kravtsova; N.H. Kaminska; A.V. Pulyaeva (Kherson State University, 2012)
In work questions of use of spreadsheets MS Excel for dynamic database creation with the enclosed structures are examined.